Kinetics and prognostic value of soluble VCAM‐1 in ST‐segment elevation myocardial infarction patients. Issue 2 (8th February 2021) - Hayek, Ahmad; Paccalet, Alexandre; Mechtouff, Laura; Da Silva, Claire C.; Ivanes, Fabrice; Falque, Hadrien; Leboube, Simon; Varillon, Yvonne; Amaz, Camille; de Bourguignon, Charles; Prieur, Cyril; Tomasevic, Danka; et al.
Abstract: Background: Soluble vascular cell adhesion molecule‐1 (sVCAM‐1) is a biomarker of endothelial activation and inflammation. There is still controversy as to whether it can predict clinical outcome after ST‐elevation myocardial infarction (STEMI). Our aim was to assess the sVCAM‐1 kinetics and to evaluate its prognostic predictive value. Method: We prospectively enrolled 251 consecutive STEMI patients who underwent coronary revascularization in our university hospital. Blood samples were collected at admission, 4, 24, 48 h and 1 month after admission. sVCAM‐1 serum level was assessed using ELISA assay. All patients had cardiac magnetic resonance imaging at 1‐month for infarct size (IS) and left ventricular ejection fraction (LVEF) assessment. Clinical outcomes were recorded over 12 months after STEMI. Results: sVCAM‐1 levels significantly increased from admission up to 1 month and were significantly correlated with IS, LVEF, and LV end‐systolic and diastolic volume. (H48 area under curve (AUC) ≥ H48 median) were associated with an increased risk of adverse clinical events during the 12‐month follow‐up period with a hazard ratio (HR) = 2.6 (95% confidence interval [CI] of ratio = 1.2–5.6, p = .02). The ability of H48 AUC for sVCAM‐1 to discriminate between patients with or without the composite endpoint was evaluated using receiver operating characteristics with an AUC at 0.67 (0.57–0.78, p = .004). This ability was significantly superior to H48 AUC creatine kinase ( p = .03). Conclusions: In STEMI patients, high sVCAM‐1 levels are associated with a poor clinical outcome. sVCAM‐1 is an early postmyocardial infarction biomarker and might be an interesting target for the development of future therapeutic strategies. Abstract : A graphical presentation summarizing the putative key role of sVCAM‐1 after ST‐elevation segment MI. MI: myocardial infarction, MMP: matrix metalloproteinase, oxLDL: Oxidized Low‐Density Lipoprotein, VCAM‐1: vascular cell adhesion molecule 1.